Genetic variability of submergence tolerance in rice related to yield and yield contributing traits: Submergence tolerance in rice - Islam, Md Rafiqul (Journal of Plant Stress Physiology)
Twenty-three rice genotypes were evaluated during kharif II season for understanding the submergence tolerance associated with short-duration and high yielding traits. For this, relative performance of seven quantitative plant traits of the genotypes viz. days to maturity, panicles per hill, panicle weight, spikelets sterility, spikelets per panicle, 1000-seed weight and grain yield were analyzed under normal and submerged conditions. The genotypic variation was found in all the relative plant traits. Multivariate techniques viz. k-means cluster analysis and discriminant function analysis (DFA) were used for grouping the genotypes. Maximum number of genotypes (15) were grouped in cluster 3 followed by cluster 1 (4). The genotype BRRI dhan31, BRRI dhan39, BRRI dhan56 and BRRI dhan57 under cluster 1 performed better compared to other cluster members. DFA showed that function 1 and 2 explained 80.5 percent and 16.9 percent respectively with a cumulative of 97.4 percent of total variance of the genotypes. Panicles per hill, panicle weight, sterility percent, 1000-grain weight and grain yield mostly contributed in grouping the genotypes. The panicle weight followed by grain yield played the major role for the maximum variance in the genotypes. The results suggest that the short-duration genotypes BRRI dhan33 and BRRI dhan56 and BRRI dhan57 performed better under submerged condition and the plant traits like panicle weight or grain yield could be the best choice for submergence tolerance in rice.